2003
DOI: 10.2170/jjphysiol.53.313
|View full text |Cite
|
Sign up to set email alerts
|

Postextrasystolic Contractility Normally Decays in Alternans in Canine In Situ Heart

Abstract: We have reported that left ventricular (LV) contractility in terms of end-systolic maximum elastance (E max , end-systolic pressure/volume ratio) always decays in alternans within 5-6 postextrasystolic (PES) beats in the canine excised, cross-circulated heart [1,2]. We have confirmed that this holds consistently under widely changed end-diastolic volume, heart rate above 80-100 beats/min, and temperature (33-38°C) as well as under intracoronary infusions of Ca 2ϩ , catecholamines, pentobarbital, and ryanodine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
3
2
Order By: Relevance
“…This difference between E max and LVP, however, existed in the previous study on canine in situ ejecting hearts [14]. These results contrast to the proportional PES alternans decays of both E max and LVP in canine isovolumic LVs at a given LVV [1][2][3][4][5][6].…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…This difference between E max and LVP, however, existed in the previous study on canine in situ ejecting hearts [14]. These results contrast to the proportional PES alternans decays of both E max and LVP in canine isovolumic LVs at a given LVV [1][2][3][4][5][6].…”
Section: Discussioncontrasting
confidence: 74%
“…Although the PES alternans decays of the systemic arterial pressure and peak LVP have been occasionally observed clinically, to the best of our knowledge the present study is the first one reporting on the LV PES E max alternans in human hearts. This study thus demonstrates that human hearts share the same type of PES E max alternans decay as those observed in canine hearts either ex vivo isovolumic [1][2][3][4][5][6] or in situ ejecting [14]. Although we did not observe an exponential or monotonic decay of PES E max in the studied patient hearts with a spontaneous ES during the diagnostic examination, the present study does not exclude the possibility of the exponential decay of the PES Emax in human hearts.…”
Section: Discussioncontrasting
confidence: 50%
“…It has been generally believed that PES contractility potentiation would decay exponentially in normal hearts under physiological conditions [26]. However, we have already reported that PESP usually decays in alternans in the canine excised, cross-circulated heart [9], and even in the canine in situ heart [11], which is more physiological than the excised, cross-circulated one. The present results also confirm the phenomenon.…”
Section: Discussionmentioning
confidence: 86%
“…
(PES) potentiation (PESP) is generally observed in isolated cross-circulated canine hearts [9,10] and in open-chest in situ hearts [11].On the other hand, the transient alternans of contractility obviously affects the alternans amplitudes of arterial pressure (AP) and left ventricular (LV) pressure (LVP) to various extents, depending on the cardiodynamic factors [1,3]. However, it remains uncertain which and how cardiodynamic factors affect the amplitude of alternans.
…”
mentioning
confidence: 99%
See 1 more Smart Citation